Evaluation of plants’ response to activated biochar through visual and proximal sensing monitoring - I. Orlandella; K.N. Smith; E. Belcore; R. Ferrero; M. Pugliese; F. Berruti; M. Piras; S. Fiore (Biomass and Bioenergy, 2026)

Application of droplet digital PCR for the detection of fish DNA in food products - S. Cau; B. Soro; R. Melillo; G. Piras; S. Salza; T. Tedde; F. Pinna; B. Vodret; C. Spanu (Food Research International, 2025)

Bridges monitoring and assessment using an integrated bim methodology - D. Rodriguez Polania; F. Tondolo; A. Osello; M. Piras; V. Di Pietra; N. Grasso (Innovative Infrastructure Solutions, 2025)
Risk assessment of long-existing infrastructure has become one of the main challenges in civil engineering. Major efforts have been made in recent years to develop new techniques for rapid damage identification and ensure proper management of these structures. This paper presents a data management approach utilizing BIM methodology to create a digital database for bridge monitoring procedures. Initially, two BIM methodologies for creating a damage database are introduced, focusing on beams from a dismantled urban viaduct. Subsequently, the most suitable methodology is applied to an existing bridge in Turin, Italy. Through the chosen methodology a damage identification and classification process based on a triangular mesh is performed, assisted by a convolutional neural network (CNN) for automatic damage detection. Additionally, the paper outlines a digitalization process within a BIM environment, integrating official guidelines for bridge risk evaluation, classification, and monitoring in Italy. By employing programming tools, all data required by the guidelines is efficiently incorporated into the database. The outcomes demonstrate the effectiveness of remote sensing applications for bridge inspection and the possibility of merging BIM methodology into the inspection process to enhance the damage assessment of existing structures.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Influence of the MCT1-T1470A polymorphism (rs1049434) on repeated sprint ability and blood lactate accumulation in elite football players: a pilot study - M. Massidda; L. Flore; N. Kikuchi; M. Scorcu; F. Piras; P. Cugia; P. Cięszczyk; F. Tocco; C. M. Calò (European Journal of Applied Physiology, 2021)

Cerebellar Structural Variations in Subjects with Different Hypnotizability - E Picerni; EL Santarcangelo; D Laricchiuta; D Cutuli; L Petrosini; G Spalletta; F Piras (The Cerebellum, 2019)

New Mediterranean Biodiversity Records (December 2012) - M. THESSALOU-LEGAKI; O. AYDOGAN; P. BEKAS; G. BILGE; Y.O. BOYACI; E. BRUNELLI; V. CIRCOSTA; F. CROCETTA; F. DURUCAN; M. ERDEM; A. ERGOLAVOU; H. FILIZ; et al. (Mediterranean Marine Science, 2012)
This paper presents records extending or confirming the distribution of Mediterranean species. Three alien algae are included, namely Codium taylorii reported for the first time from the Aegean and Turkey (Izmir Gulf), Caulerpa racemosa var. cylindracea (Karpathos and Chalki Isl., Aegean Sea) and Ganonema farinosum (Karpathos Isl., Aegean Sea). As far as animals are concerned, Litarachna divergens (Acari: Hydrachnidia) was recorded (Side, Eastern Mediterranean) and represents a new amendment at genus level for Turkish fauna. Other invertebrates include alien species such as the crabs Dyspanopeus sayi (Lago Fusaro, SW Italy), Percnon gibbesi (Larnaca, Cyprus; Karpathos and Chalki Isl., Aegean Sea) and Callinectes sapidus (Voda estuary, NW Greece), the nudibranch Aplysia dactylomela (Boka Kotorska Bay, Montenegro), the gastropod Conomurex persicus (Karpathos and ChalkiIsl., Aegean Sea) and the bryozoan Electra tenella (Livorno harbour and Messina Straits area). The alien fish Siganus luridus, Siganus rivulatus, Fistularia commersonii, Sphyraena chrysotaenia and Sargocentron rubrum are also reported from the islands of Karpathos and Chalki, and Pteragogus pelycus from Heraklion Bay, Crete. In addition, new localities for four rare Mediterranean inhabitants are given: the cephalopod Thysanoteuthis rhombus (NW Sardinia) and the fish: Lampris guttatus (Calabria, S Italy), Petromyzon marinus (Gokova Bay) and Remora australis (Saronikos Gulf), while the opisthobranch gastropod Cerberilla bernadettae is reported for the first time from the E Mediterranean (Cyprus). Finally, three species of the Aegean ascidiofauna are recorded for the first time: Lissoclinum perforatum, Ciona roulei and Ecteinascidia turbinata. Furthermore, it was established that Phallusia nigra has extended its distributional range to the north of the Aegean Sea.

Species accumulation over space and time in European Plio-Holocene mammals - P. Raia; F. Carotenuto; C. Meloro; P. Piras; C. Barbera (Evolutionary Ecology, 2011)